Decision Support Systems for Risk-Based Management of Contaminated Sites - Marcomini, Antonio; Suter II, Glenn Walter; Critto, Andrea; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Decision Support Systems for Risk-Based Management of Contaminated Sites addresses decision making in environmental risk management for contaminated sites, focusing on the potential role of decision support systems in informing the management of chemical pollutants and their effects. Considering the environmental relevance and the financial impacts of contaminated sites all over the post-industrialized countries and the complexity of decision making in environmental risk management, decision support systems can be used by decision makers in order to have a more structured analysis of a problem at hand and define possible options of intervention to solve the problem. Accordingly, the book provides an analysis of the main steps and tools for the development of decision support systems, namely: environmental risk assessment, decision analysis, spatial analysis and geographic information system, indicators and endpoints. Sections are dedicated to the review of decision support systems for contaminated land management and for inland and coastal waters management. Both include discussions of management problem formulation and of the application of specific decision support systems. This book is a valuable support for environmental risk managers and for decision makers involved in a sustainable management of contaminated sites, including contaminated lands, river basins and coastal lagoons. Furthermore, it is a basic tool for the environmental scientists who gather data and perform assessments to support decisions, developers of decision support systems, students of environmental science and members of the public who wish to understand the assessment science that supports remedial decisions.
Basic Steps for the Development of Decision Support Systems -- Environmental Risk Assessment -- Decision Support Systems and Environment: Role of MCDA -- Spatial Analytical Techniques for Risk Based Decision Support Systems -- Indicators and Endpoints for Risk-Based Decision Processes with Decision Support Systems -- Contaminated Land: A Multi-Dimensional Problem -- Decision Support Systems for Contaminated Land Management: A Review -- A Spatial Decision Support System for the Risk-Based Management of Contaminated Sites: The DESYRE DSS -- SMARTe: An MCDA Approach to Revitalize Communities and Restore the Environment -- DSS-ERAMANIA: Decision Support System for Site-Specific Ecological Risk Assessment of Contaminated Sites -- SADA: Ecological Risk Based Decision Support System for Selective Remediation -- Decision Evaluation for Complex Risk Network Systems (DECERNS) Software Tool -- Decision Support Systems (DSSs) for Contaminated Land Management #x2013; Gaps and Challenges -- Use of Decision Support Systems to Address Contaminated Coastal Sediments: Experience in the United States -- Review of Decision Support Systems Devoted to the Management of Inland and Coastal Waters in the European Union -- MODELKEY: A Decision Support System for the Assessment and Evaluation of Impacts on Aquatic Ecosystems -- CADDIS: The Causal Analysis/Diagnosis Decision Information System -- BASINS: Better Assessment Science Integrating Point and Nonpoint Sources -- A Decision Support System for the Management of the Sacca di Goro (Italy) -- Decision Support Systems (DSSs) for Inland and Coastal Waters Management #x2013; Gaps and Challenges.
Keywords: Environment; Geographical information systems; Environmental management; Ecotoxicology; Pollution; Environmental economics; Environment; Pollution, general; Environmental Management; Geographical Information Systems/Cartography.; Ecotoxicology; Environmental Economics; Electronic books